Intersectionality of Politics and Religion In Global Populism Towards Covid-19 Pandemic Responses - Nuraeni, Nuraeni; Habibah, Yasmin Nur (The Sunan Ampel Review of Political and Social Sciences, 2022)
COVID-19 has forced all countries to implement various policies to reduce the number of spreads. The biggest challenges in handling the pandemic mostly come from the public's perception towards COVID-19, which turns out to follow the same pattern or even strongly influenced by political views and religious beliefs where both meet in a populist trend. Even before the pandemic, a rife outbreak of populism had colored the world. Presidential elections in the US, Brexit in Europe, and the presidential election in Indonesia have become a battleground for populist views that have created such polarization. The polarization hinders most of the implementations of government policies and has also affected the handling of the pandemic. Besides that, the existing polarization in society has been aggravated by the growing distortion and misinformation regarding COVID-19. Even when, scientifically, the COVID-19 vaccine can be made and distributed. Conspiracy theories with political and religious backgrounds are the most widely used basis for doubts about the reality and handling of COVID itself. Even worse, various groups do not believe in COVID-19 or refuse vaccines, even in the high-literacy countries. This paper will examine the general symptoms of global populism in the context of the pandemic. The authors argue that this becomes a more complicated challenge for countries than making a vaccine or finding medicines in stopping the COVID-19 pandemic.